(untitled) (Al-Academy, 2015)
Although the majority of trends confirm the design aspects of the performance, functional and aesthetic design of the product. However, the attention was more focused on the nature of the plastic for those results, it is through the appearance of formal and guaranteed career such as designing Achieved adopt us the extent of the impact Relations Association between the elements and principles of design to achieve complementarity in the completed design of aesthetic and functional significance expressive and symbolic and in doing so has introduced a lot of new concepts for the arrangement and organization, coordination and functional classification of the unfinished design gave way to show diversity trends in the design of industrial products, according to the value of functionality and aesthetic addition to the specifications of the raw material, organization and composition of the design, which featured creations design in done through the introduction of changes in the systems of formal and functional in the construction design of the accomplishment associated with the function of the design and the accompanying technical evolution of the material is a necessity in the maturing design idea. Through an initial exploratory study researcher of industrial products performed locally in the city of Baghdad, the researcher found that there is a problem standing in front of the concept of complementarity in terms of construction and relations between the Association and the meaning of integration based on the basis of the dimensions of the aesthetic and functional design is finished